Valorizing apple by-products as emulsion stabilizers: Experimental design for modeling the structure-texture relationships. (December 2020) - Huc-Mathis, D.; Guilbaud, A.; Fayolle, N.; Bosc, V.; Blumenthal, D.
Abstract: Apple pomace was tested for its stabilizing properties of emulsions, among 15 formulas organized as an experimental design with 4 factors: oil content, powder content, polymer content and time. A wide range of texture (viscosity at 10s −1 from 200 to 7500 mPa s) and oil droplet size (from 18 to 46 μm) was achieved. This strategy enlightened that oil, and in a lesser extent, polymer content, mainly drove the texture of the emulsions. The polymer content was the most significant parameter influencing the shear-thinning behavior of the emulsions (– 0.247). The amount of powder displayed a strong and significant negative impact on the oil droplet diameter (−1.007). A linear trend was even obtained between 1/droplet diameter and the powder amount. A good stability was achieved for 12 formula among the 15, with no coalescence nor drainage obtained in the emulsions, even when submitted to accelerated aging. A scale-up was even possible from a lab 200 mL version of emulsion to a semi pilot version of 12 L. This study thus revealed the ability of some food by-products to be valorized as sole emulsion stabilizer, without any chemical modification, extraction, purification of fractionation, ensuring a virtuous circle. Highlights: Minimal-processed apple powder can stabilize a wide range of emulsions over 2 months. The powder amount drives the oil droplet diameter (linear relationship 1/D = f(mp )). The oil content and addition of biosourced polymer drive the emulsion rheology. Predictive models are obtained for droplet size, gel strength and viscosity. Proof of concept is obtained for scaling-up from 200 mL to 12 L.